La/Ba-based cobaltites as IT-SOFC cathodes: a discussion about the effect of crystal structure and microstructure on the O2-reduction reaction - Garcés, Diana Andrea; Soldati, Analía Leticia; Troiani, Horacio Esteban; Montenegro Hernandez, Alejandra; Caneiro, Alberto; Mogni, Liliana Verónica (Pergamon-Elsevier Science Ltd, 2016)
Fil: Garcés, Diana Andrea. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte; Argentina. Comisión Nacional de Energía Atómica. Centro Atómico Constituyentes; Argentina